Agricultural terrorism and food insecurity in Indonesia: a policy analysis - Utami, Raden Roro Mega; Puspitasari, Maria (Technium Social Sciences Journal, 2023)
As a form of bioterrorism, agricultural terrorism/agroterrorism leads to livestock and crop interventions. Agroterrorism is part of economic warfare, which involves the destruction of a country's agricultural or ecological infrastructure using biological weapons. Agroterrorism leads to a country's food insecurities and the collapse of its economic climate. The development of biotechnology allows the modification of biological elements to result in changes in the characteristics of living things infiltrated by these agents. Genetically Modified Organism (GMO) technology, for instance, is a paradoxical double-edged sword. GMOs can generate economic benefits, but can also result in huge economic losses if they are weaponized as agroterrorism. Using a qualitative approach, this study conducts a policy analysis to explain the factors that impact the absence of food safety policies from agroterrorism threats in Indonesia. Data collection was conducted through literature searches in the form of articles, documents, and policies with the keywords "agricultural terrorism"; "Genetically Modified Organism"; "food insecurity"; "biotechnology", and "national security"; as well as by analyzing the experiences of other countries. As a country with direct land borders with other countries, Indonesia needs extra efforts to secure the country's biodiversity. As one of the consequences of the ASEAN-China free trade, the possibility of agroterrorism events has become more likely to occur in Indonesia. The development of a solid food infrastructure may overcome this problem. Recommendations for safe and resilient food policy scenarios should be pursued to ensure quality food production and sustainable economic growth for a better Indonesia, not only in the present, but for the sake of sustainability in the future.